Phenology of Flowering and Pod Maturity on Some Cocoa Clones (Theobroma cacao L) - Indah Anita Sari; Agung Wahyu Susilo (Indonesian Coffee and Cocoa Research Institute, 2015)
Phenology of flowering is an important aspect in the growth cycle of cocoa (Theobroma cacao L.) because the performance of plant especially flowering is linked with anthesis time, time and duration of stigma receptivity, fruit formation, crossing, and seed development which determine the plant breeding programs . Research was conducted at the Kaliwining experimental station of Indonesian Coffee and Cocoa Research Institute (ICCRI). The cocoa plant was originated from top grafting seedling with the age of eight years. Design of experiment was randomized complete block design consisted of eight clones as treatment with three replications. Each plot consisted of 20 sample flowers. The parameters observed were phenology of flowering and pod maturity. Phenology of flowering observed were age of flowering, number of opened flower buds, number of flower buds that dropped before being opened, number of flower buds that dropped after being opened, and number of opening flowers that developed into tiny fruits. Observation on pod and been quality was done on pod size, pod weight, pod length, pod girth, and bean number. The result of experiment showed that difference in phenologyof flowering and age of pod maturity existed within eight cocoa clones tested. KKM 22 showed the shortest flowering age and pod maturity, and lowest number of beans. The highest success of pollination was observed on Sca 6 and KW 617. ICCRI 03, Sulawesi 03, ICCRI 07, KKM 22 and KW 617 showed relative low success of pollination, that iswas between 10 to 17.6%. Age of flower opening did not significantly influence age of pod maturity, on the other hand it did not negatively influence percentage of flower opening and percentage of pollinated flowers. The characteristic of flowering age had high genetic coefficient of variation as well as high estimated value of heritability. Percentage number of flower buds that dropped before open showed high genotypic and phenotypic coefficient of variation, however the estimated heritability was grouped in low category. The characteristic of pod maturity age, percentage of flower opening and bean number in each pod had low values of genotypic and phenotypic coefficient of variation,and low heritability.